OPERATIONAL OF SOLID WASTE HANDLING IN SUBANG DISTRICT - Salman, Nurcholis (Journal of Community Based Environmental Engineering and Management, 2021)
The operational technique of waste management in Subang Regency uses simulations in the form of three scenarios, namely scenario-1 is a scenario that has been running so far (existing), in which recycling activities have not yet developed, so it is practically only a collection-transport-disposal system. a better scenario than Scenario-1, in which there are already recycling activities in the TPA, both in the formal and informal sectors (scavenging) and Based on the projections for each scenario above, it is found that Scenario-3 is a moderate scenario, because: the volume of waste transportation to the landfill is the minimum, the volume of waste that must be removed to the landfill is also the minimum which automatically has the minimum volume of landfill among the 3 (three) proposed scenarios. This scenario makes the transportation system efficient, but requires a larger investment to facilitate facilities and infrastructure. However, this is not the case in Scenario-1, in this scenario, the budget required for the procurement of facilities and infrastructure is relatively lighter than the needs in the other two scenarios.